1998
DOI: 10.1046/j.1365-2249.1998.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of CD57+ T cells in knee joints and adjacent bone marrow of rheumatoid arthritis (RA) patients: implication for an anti-inflammatory role

Abstract: The distribution of CD57+ T and CD56+ T cells in patients with RA was examined. In control osteoarthritis patients, these cells exist as a minor population in the peripheral blood. Our data show that in patients with RA, CD57+ T cell levels are elevated in peripheral blood, knee joint fluid, knee synovial membrane and bone marrow (BM), compared with peripheral blood of controls. CD57+ T cells are especially high in knee joint fluid and joint‐adjacent BM, while CD56+ T cells show no such increase. CD57+ T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
2
29
2
2
Order By: Relevance
“…However, some previous reports have provided data implying a suppressive role of CD57ϩ T cells against the inflammation of RA and other diseases, as well as against inflammation arising from normal immune responses (7,16). In contrast to our findings, Arai et al found an inverse relationship between ESR and the proportion of CD57ϩ T cells in the joint fluid of RA patients (7).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, some previous reports have provided data implying a suppressive role of CD57ϩ T cells against the inflammation of RA and other diseases, as well as against inflammation arising from normal immune responses (7,16). In contrast to our findings, Arai et al found an inverse relationship between ESR and the proportion of CD57ϩ T cells in the joint fluid of RA patients (7).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, Arai et al found an inverse relationship between ESR and the proportion of CD57ϩ T cells in the joint fluid of RA patients (7). The discrepancy between the findings of Arai et al and our current findings could be attributable to the difference in T cell subsets (CD4/ CD8) studied.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations